2018
DOI: 10.1002/mame.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heterocyclic Aramid Fiber Based on Solid‐Phase Cross‐Linking of Oligomers with Reactive End Group

Abstract: Low compressive strength of aramid fiber is one of the major obstacles for its application in advanced composite materials. In this study, poly‐(benzimidazole‐terephthalamide) (PABI) fibers are fabricated by solid‐phase cross‐linking of corresponding oligomers end‐capped with norbornene anhydride (NA). Concentration of the spinning solution increases and apparent viscosity is reduced significantly through this method, which improves its processability. Reactivity and thermal stability of the NA group are measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The probability that fibril will not peel off is basically 60%. In our previous study, fiber with sufficient crosslinking did not show damage after pull‐out test and this was mainly attributed to enhancement of intermolecular interaction through crosslinking . Because crosslinking degree of AF‐70 and AF‐100 is comparatively higher than that of other samples, which can bring about stronger interaction among polymer chains, it is concluded that fibril detachment is effectively avoided due to stronger intermolecular interaction of AF‐70 and AF‐100.…”
Section: Resultsmentioning
confidence: 90%
“…The probability that fibril will not peel off is basically 60%. In our previous study, fiber with sufficient crosslinking did not show damage after pull‐out test and this was mainly attributed to enhancement of intermolecular interaction through crosslinking . Because crosslinking degree of AF‐70 and AF‐100 is comparatively higher than that of other samples, which can bring about stronger interaction among polymer chains, it is concluded that fibril detachment is effectively avoided due to stronger intermolecular interaction of AF‐70 and AF‐100.…”
Section: Resultsmentioning
confidence: 90%
“…Conventional methods to improve the compressive strength mainly concentrate on introducing chemical cross‐linking among macromolecular chains, which can enhance intermolecular interaction throughcovalent bond . Trace amount of oxygen was introduced into heat‐treatment process of aramid fiber to make it cross‐link .…”
Section: Figurementioning
confidence: 99%
“…Two obvious peaks appearing at nearly 2818 and 3047 cm −1 can be observed for DPAA−H. They can be assigned as υ s (‐CH‐) and υ s (=CH‐),, which indicates that (‐C≡CH) converts into (‐CH‐) and (=CH‐) after reaction. So, the cross‐linking structure of DPAA−H is presumed and shown in Figure c.…”
Section: Figurementioning
confidence: 99%
“…[15] However, additionally introducing hydrogen bonding interaction is limited since pristine PIBA fibers have been equipped with ample hydrogen bonds between polymer chains. [16,17] Although strong inter-chain interaction based on chemical crosslinking can increase the shear strength between polymer chains and has pronounced effect on the enhancement of compressive strength of fibers, [18][19][20][21] the reducing crystallinity and orientation degree of fibers lead to restricted improvement of tensile strength, even deteriorating strength sometimes. [18] Thus, realizing the effective stress transfer between polymer chains without sacrificing structural integrity of PBIA fibers is an ongoing challenge.…”
Section: Introductionmentioning
confidence: 99%